The influence of Customer Relationship Management (CRM) and service quality on customer satisfaction and its impact on customer loyalty: A case study on PPJK PT. Pusaka Golden Trans Utama - Makatita, Desmawati (Priviet Social Sciences Journal, 2025)
This study investigates the effect of Customer Relationship Management (CRM) and service quality on customer satisfaction and their implications for customer loyalty at PPJK PT. Pusaka Golden Trans Utama, a customs clearance service company in Jakarta. This study is positioned within the increasingly competitive service environment of export–import facilitation, where firms are required to provide efficient operational support and maintain long-term customer relationships. This study focuses on four core constructs, namely CRM, service quality, customer satisfaction, and customer loyalty, to explain how relationship- and service-based strategies contribute to sustainable business performance in the customs brokerage sector. This study employed a descriptive quantitative design. Data were collected from 100 customers of PPJK PT. Pusaka Golden Trans Utama using questionnaires, supported by observation, interviews, and documentation. The sample was determined using the Slovin formula and selected using simple random sampling. Path analysis was used to test both direct and indirect effects among variables. The findings indicate that CRM and service quality positively and significantly affect customer satisfaction. CRM and service quality also directly influence customer loyalty, while customer satisfaction contributes positively to loyalty and serves as an intervening variable in the relationship between independent variables and loyalty. Among the tested predictors, service quality appears to exert the strongest influence, particularly in shaping customer satisfaction and reinforcing the loyalty. These findings confirm that effective customer relationship practices and consistently high service quality are essential for strengthening customer trust, improving satisfaction, and sustaining loyalty in customs service companies. The study concludes that companies in the customs clearance sector should prioritize relationship-based service strategies and continuous service quality improvement to remain competitive and retain customers in the long term.